USE OF SUBTERRANEOUS WATER IN URBAN AREA OF FREDERICO WESTPHALEN - RS - Kemerich, Pedro Daniel da Cunha; Borba, Willian Fernando de; Preto, Pablo Ricardo Picetti; Fernandes, Gabriel D'Ávila; Benso, Marcos; Flores, Bruno Acosta; Dornelles, Henrique; Flores, Carlos Eduardo Balestrin (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
With an increase in the contamination of water resources, surface and underground, there is great concern about the health of the population that consumes water out of potability standards. Based on this, the present study aims to register the alternative sources of water supply in the city of Fredericksburg - RS, in order to be aware of the portion of the population that uses for drinking water from such sources. Data collection was performed with visits to homes where they were raised about the conditions of water consumption and social population. In urban, neighborhoods Barrel Panosso, Itapagé, Aparecida, Fatima, St. Anthony, St. Ignatius, Ipiranga and Garden Center SPRING, were registered to a total of 71 alternative sources of supply, being 6 source / spring, 5 wells and 60 dug wells. Based on these results, we found that despite having access to the public water supply, many users still opt for alternative sources, which in many cases have very poor condition potability